Relationship of Knowledge, Attitudes, and Preventive Actions to The Incidence of HIV-AIDS in the Men Who Have Sex with Men (MSM) in the Oebobo District Kupang City - Refandro Purumbawa; Petrus Romeo; Helga J. N. Ndun (Universitas Nusa Cendana, 2022)
Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS), a sexually transmitted disease, is one of the world's most serious health problems including in East Nusa Tenggara, Indonesia. HIV-AIDS disease can be prevented by being faithful to a sex partner and using condoms during sexual intercourse.